2005
DOI: 10.2337/diacare.28.7.1745
|View full text |Cite
|
Sign up to set email alerts
|

Birth Weight and Parental BMI Predict Overweight in Children From Mothers With Gestational Diabetes

Abstract: OBJECTIVE -To investigate the growth of children from pregnancies with gestational diabetes mellitus (GDM) and its association with antenatal maternal, fetal, and recent anthropometric parameters of mother and father. RESEARCH DESIGN AND METHODS -In 324 pregnancies of Caucasian womenwith GDM, BMI before pregnancy, maternal glycemic values, and measurements of the fetal abdominal circumference were recorded. The weight and height of infants were measured at birth and at follow-up at 5.4 years (range 2.5-8.5). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
109
3
19

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(150 citation statements)
references
References 27 publications
16
109
3
19
Order By: Relevance
“…We have demonstrated that in the normoglycemic popu- lation, the impact of glycemia on offspring growth is transient, as it is not detectable at 12 weeks of age. This is in keeping with findings that despite improvements in the glycemic management of diabetic pregnancies in recent years, there has been no decrease in the risk of obesity in the offspring of mothers with diabetes (21), and in a cohort of mothers with well controlled gestational diabetes, their fasting glycemia was not a major determinant of childhood obesity (22).…”
Section: Multiple Linear Regression Analysissupporting
confidence: 87%
“…We have demonstrated that in the normoglycemic popu- lation, the impact of glycemia on offspring growth is transient, as it is not detectable at 12 weeks of age. This is in keeping with findings that despite improvements in the glycemic management of diabetic pregnancies in recent years, there has been no decrease in the risk of obesity in the offspring of mothers with diabetes (21), and in a cohort of mothers with well controlled gestational diabetes, their fasting glycemia was not a major determinant of childhood obesity (22).…”
Section: Multiple Linear Regression Analysissupporting
confidence: 87%
“…The Lifeways study was one of the first to show that general practitioner-reported wheeze or asthma (52) Czech Republic 7577 1994 x Devereux et al (53) UK 1400 1997 x x Drouillet et al (54) France 1900 2003 x x x x Dubois et al (55) Canada 1450 1998 x x Eggesbo et al (56) Norway 2500 2003 x x x Emanuel et al (57) UK 3076 1958 x Gorden-Larsen et al (58) USA 14 706 1995 x Gracie et al (59) Canada 3388 2008 x x Grandjean et al (60) Faroe Islands 1022 1986 x x x x Guldner et al (61) France 4000 2002 x x Guxens et al (62) Spain 3768 1997 x x x x x Grazuleviciene et al (63) Lithuania 4405 2007 x Hawkes et al (64) Ireland 2185 2008 x Hawkins et al (65) UK 13 113 2000 x Hill et al (66) Wales 420 2009 x x Hryhorczuk et al (67) Ukraine 4510 1992 x x x Hui et al (68) Hong Kong 8327 1997 x x Hunt et al (69) Canada 521 1981 x x Inskip et al (70) UK 3159 1998 x x Jaddoe et al (71) Netherlands 10 000 2002 x Jedrychowski et al (72) Poland 432 2000 x x Kaplowitz et al (73) UK 224 1986 x x Karvonen et al (74) Finland 442 2002 x x x x Katier et al (75) Netherlands 2500 (95) Germany 2000 2011 x x x x Richiardi et al (96) Italy 7500 2005 x x x x Schaefer-Graf et al (97) Germany 324 1995 † x x Sekine et al (98) Japan 8941 1992 x x Skalkidou et al (99) Sweden 580 2009 x x Tsuchiya et al (100) Japan 1260 2007 x x van Eijsden et al (101) The Netherlands 6161 2003 x x x x Vandentorren et al (102) France 20 000 2011 x x x Vecchi Brumatti et al (103) Italy 900 when the child averaged 3 years was inversely associated with maternal fruit and vegetable and fish consumption during pregnancy (1...…”
Section: Dietary Patterns and Risk Of Childhood Wheezing Or Asthmamentioning
confidence: 99%
“…Infants from GDM pregnancies born with normal weight still had a rate of 67% childhood overweight when both parents were obese in contrast to 19% overweight children when both parents had a BMI <30 kg/m2. (15).…”
Section: Diabetes In Pregnancymentioning
confidence: 99%